Tasa de abandono del tratamiento con Anti-VEGF en pacientes con degeneración macular relacionada con la edad de tipo neovascular (DMREn) en Buenos Aires, Argentina - Pablo Franco; Alejandro Suwezda; Aníbal Francone; Patricio Schlottmann (Archivos Argentinos de Oftalmología, 2024)
IntroductionThe neovascular aged macular degeneration (nAMD) is characterized by the abnormal growth of choroidal vessels beneath the macula that disruptsthe anatomy and function of the neurosensory retina, leading to severe and irreversible vision loss.Currently, the treatment of choice in patients diagnosed with nAMD is intravitreal injections of molecules that block vascular endothelial growth factor (VEGF)3,4. The frequent treatment and follow-up requirements place a great burden on patients and their significant others. This often leads to problems of adherence and consistency of treatment.To date, there are no data available on adherence to treatment in patients with nAMD in Argentina.Adherence studies in Latin America can help to identify the main limitations to address the difficulties of patients with nAMD in our setting.Materials and methodRetrospective cohort study including patients with a diagnosis of nAMD who received their first Anti-VEGF treatment between 01-JAN-2014 and 31-DEC-2014 in 3 ophthalmology centers in Buenos Aires, Argentina. Individuals who met the dropout criteria were contacted by telephone and, if they agreed to participate, answered a questionnaire.ResultsA total of 252 patients were included. Of which 154 were women (61.1%). The mean age was 79.1 ± 8.7. The average dropout rate at 5 years was 29.4%. The variables associated with the highest dropout rate were male sex (HR: 0.616), low baseline visual acuity (logmar visual acuity, HR: 2.032) and public eye care center (HR: 0.234).DiscussionThe 5-year dropout rate for the 3 centers combined was 29.4%. The public dropout rate was 63.8% vs. only 28.7% for the private sector. This could berelated to the coverage and access to the treatment.This, together with the causes of abandonment described above, demonstrates the need for more accessible drugs capable of increasing theinterval between visits.